2013
DOI: 10.1016/j.matlet.2013.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Fe-coordinated diamino-functionalized SBA-15 with hierarchical porosity for phosphate removal

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Abstract: Hierarchically macroporou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, the efforts for exploiting new adsorbents, improving the removal efficiency of adsorbents and developing an ideal adsorption system have never been stopped. Recently, researchers found that functionalized mesoporous silica materials, such as Fe(III)-coordinated amino-functionalized SBA-15, have exhibit enhanced phosphate removal capacity, due to their large surface areas, accessible Fe(III) active sites as well as controllable pore sizes and arrangements [8,9].…”
Section: Open Accessmentioning
confidence: 99%
“…However, the efforts for exploiting new adsorbents, improving the removal efficiency of adsorbents and developing an ideal adsorption system have never been stopped. Recently, researchers found that functionalized mesoporous silica materials, such as Fe(III)-coordinated amino-functionalized SBA-15, have exhibit enhanced phosphate removal capacity, due to their large surface areas, accessible Fe(III) active sites as well as controllable pore sizes and arrangements [8,9].…”
Section: Open Accessmentioning
confidence: 99%
“…29,30 In particular, the hollow particles with a controlled interior void space and mesoporous shell structure have exhibited a number of advantageous features, including a low density, high surface area, stability, and surface permeability; thus facilitating use as high-performance adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Study the FT-IR spectrum of β-TCP/PLGA before and after 37 0 C incubation was carried out. The absorption bands at maximum values were 1094, 1034,603 and 564 cm -1 , from phosphate group [ 23], β-TCP. The approximately band at 3420 cm -1, as the result of OH --group and H + bonds at 1420 and 631 Cm -1 as the result of OH was attributed to the bending vibrations of OH-group.…”
Section: Results and Discussion Characterization Of Poly Lactic-co-glmentioning
confidence: 97%